2020
DOI: 10.3390/su12125170
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Research on the Fama-French Three-Factor Model and a Sentiment-Related Four-Factor Model in the Chinese Blockchain Industry

Abstract: As one of the most significant components of financial technology (FinTech), blockchain technology arouses the interests of numerous investors in China, and the number of companies engaged in this field rises rapidly. The emotion of investors has an effect on stock returns, which is a hot topic in behavioral finance. Blockchain is an essential part of FinTech, and with the fast development of this technology, investors’ sentiment varies as well. The online information that directly reflects investors’ mood cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 24 publications
(30 reference statements)
0
16
0
Order By: Relevance
“…Initially developed from bitcoin cryptocurrency, the technology of blockchain proved its value in FinTech, with deep research pathways showing their effects in stock markets (Ji et al, 2020), and in the sensitive area of financial services in banks, as knowledge-hiding can be resolved with blockchain technology and can extend knowledge-sharing (Chang et al, 2020). Progressively, other domains have recognized blockchain as being essential for improving existing systems and developing new ones.…”
Section: Blockchain and Tokenization Are The Future Of Co-creationmentioning
confidence: 99%
“…Initially developed from bitcoin cryptocurrency, the technology of blockchain proved its value in FinTech, with deep research pathways showing their effects in stock markets (Ji et al, 2020), and in the sensitive area of financial services in banks, as knowledge-hiding can be resolved with blockchain technology and can extend knowledge-sharing (Chang et al, 2020). Progressively, other domains have recognized blockchain as being essential for improving existing systems and developing new ones.…”
Section: Blockchain and Tokenization Are The Future Of Co-creationmentioning
confidence: 99%
“…Fama and French studied the factors that determine the difference of stock returns based on the American stock market in 1992, and then found that the market value, book to market ratio and P/E ratio of listed companies can explain the difference of stock returns. This multi-factor equilibrium pricing model can be expressed as: 𝑅 𝑖𝑡 − 𝑅 𝑓𝑡 = 𝛼 𝑖 + 𝛽 𝑖 (𝑅 𝑚𝑡 − 𝑅 𝑓𝑡 ) + 𝑠 𝑖 𝑆𝑀𝐵 𝑡 + ℎ 𝑖 𝐻𝑀𝐿 𝑡 + 𝜀 𝑖𝑡 (1) In this formula, 𝑅 𝑓𝑡 represents the risk-free return rate of time t, 𝑅 𝑚𝑡 represents the market rate of return at time t, 𝑅 𝑖𝑡 represents the rate of return of asset I at time t, 𝑅 𝑚𝑡 − 𝑅 𝑓𝑡 is the market risk premium. 𝑆𝑀𝐵 𝑡 is the simulated portfolio yield (small minus big) of the market value (size) factor of time t, and 𝐻𝑀𝐿 𝑡 is the simulated portfolio yield (high minus low) of the book to the market factor of time t.…”
Section: Fama-french Three-factor Model Theorymentioning
confidence: 99%
“…However, cryptocurrencies are not the only application of blockchain. It is a well-known technology fintech, along with others such as significant data machine learning and cloud computing (Ji et al , 2020). On the other hand, the economies of payment systems and financial services are affected profoundly by introducing new cryptocurrencies and blockchain technologies with functionalities like providing faster and more secure payment services.…”
Section: Introductionmentioning
confidence: 99%
“…These features can boost the performance of blockchain-based technology companies, especially those that overwhelmingly provide financial services. As a result of these unique features, an increasing number of firms have started to adapt to this technology (Ji et al , 2020).…”
Section: Introductionmentioning
confidence: 99%